RASIO KEUANGAN DALAM MEMPREDIKSI KONDISI FINANCIAL DISTRESS PERUSAHAAN TEKSTIL DAN GARMEN - Aji Sunarji; Mujibah Sufyani (Faculty of Economic and Business, University of Pasundan, 2017)
This study aims to analyze the financial ratios in predicting the condition of financial distress, and to determine the factors causing bankruptcy in textile and garment companies listed on the Indonesia Stock Exchange. The research method used to predict financial distress is by using the methods of Zmijewski (X-Score), Olhson (Y-Score), Altman (Z-Score), Grover (G-Score) and Springate (S-Score). The results showed that there were companies that ran into financial distress; five of them used Zmijewski (X-Score) method, ten of them used Olhson (Y-Score) method, nine of them used Altman (Z-Score) method, six of them used Grover (G -Score) method, and thirteen of them used the Springate (S-Score) method. Financial distress is caused by two main factors that come from internal and external. Internal factors include financial structure errors, allocation of funding resources, two consecutive losses, and poor management. External factors include government policy, market demand, poor macro conditions, and intense competition.